2003
DOI: 10.1088/0952-4746/23/3/308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiation risk and work practices during cerebral interventions

Abstract: This study was intended to evaluate radiation risk to patients during cerebral interventions and the contribution to this risk from work practices. Thirty nine patients undergoing cerebral interventions in a digital subtraction angiography suite were included in this study. Patients who underwent cerebral interventions were categorised into two groups according to the number of cerebral interventions performed on them, and their effective doses were calculated. The effective dose for patients undergoing a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, incidences of radiation-induced skin injuries have been reported in neurointerventional procedures, such as embolization of arteriovenous fistulas (AVF), [1][2][3][4] because these complicated interventional radiology procedures tend to require an extended fluoroscopic exposure time and repeated digital subtraction angiography (DSA) with various angles of x-ray projection. In addition, these procedures often need to be performed repeatedly.…”
mentioning
confidence: 99%
“…Improperly calibrated machines can also inadvertently impart large doses to patients without the knowledge of the operator. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Judicious choice of IIF such as a 40 cm IIF without adversely affecting the diagnostic information the radiologist is looking for could make a significant contribution to dose reduction. [14] Though strict radiation safety protocols are adopted in the DSA equipment, chances of recruiting higher exposure factors and radiation doses are possible if proper quality assurance is not performed to these higher end modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was necessary to assess the BSF separately and include it in the calculation of ESD. [14] The backscatter factors during the abdominal embolization varied from 1.27 to 1.39.…”
Section: Dosimetry and Calculationsmentioning
confidence: 99%